Impacto de las fuentes externas de conocimiento en la innovación de productos de empresas de baja y media baja intensidad tecnológica - Del Carpio-Gallegos, Javier Fernando (2018)
Despite their limitations, small and medium-sized companies with low and medium low technology intensiveness set themselves the challenge of improving their innovation capacity. Therefore, a probit model is proposed to study whether there is a positive effect of their external sources of market and technological knowledge on their ability to innovate in products. A sample of 826 companies listed in the National Poll on Innovation of Peru were examined. The results confirm a positive effect of external sources of knowledge, which favors the innovation of their products. These findings can help agencies promoting innovation to better focus policies to address the needs of small and medium enterprises in emerging economies.